Strategi Digital Marketing, Kualitas Pelayanan dan Inovasi Terhadap Pengambilan Keputusan Pembelian : (Studi Kasus Erenka Cafe and Space Glenmore) - Roy Subhan Tri Handika; Rio Sudirman; Teguh Purnomo (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This study aims to examine digital marketing strategies, service quality and innovation on purchasing decisions at Erenka café & space Glenmore. Based on the chosen research method, which is quantitative in nature, the findings shed light on the influence of variables on purchasing decisions at Erenka Café & Space Glenmore. Specifically, the results reveal that the Digital Marketing Strategy variable has a partial impact on customers' purchasing decisions in this establishment. On the other hand, the research findings also indicate that the Innovation variable does not significantly affect customers' purchasing decisions at Erenka Café & Space Glenmore. Simultaneously, Digital Marketing Strategy, Service Quality, and Innovation influence purchasing decisions at Erenka café & space Glenmore.